Digital audiences of union organising: A social media analysis. (23rd March 2021) - Panagiotopoulos, Panos
Abstract: The article offers a novel conceptualisation of unions' digital audiences and considers how their characteristics affect the practice of organising. Data were collected from the central Twitter accounts of 33 British unions resulting in 167, 658 tweets and information from their 357, 687 followers. Using textual and network methods, the analysis shows how unions interact with large, diverse and unexpected audiences including members, other individuals and organisations within their stakeholder groups. The findings support Twitter's role as a tool for organising in directions like stakeholder engagement and reaching new audiences. The article further discusses how unions can respond to the imagined characteristics of their digital audiences and develop an approach to engagement that builds on the relationship between audiences and content.